Health Literacy of Osteoporosis Risks among Caregivers Serving in Disability Care Facilities - Lin, Lan-Ping (Int J Environ Res Public Health, 2020)
Osteoporosis is a global public health issue and its consequent effects are a growing concern worldwide. Caregivers generally experience occupational physical ailments and they have less of a tendency to engage in preventive health behaviors, leading them to be in a higher risk group for osteoporosis. This study aims to present a general profile of health literacy related to osteoporosis risks and identify its associated factors among disability institutional caregivers. A cross-sectional study with a structured questionnaire was used to collect information on 465 caregivers from seven disability care institutions regarding their awareness of the health literacy related to osteoporosis risks. The results indicate that the average literacy score related to osteoporosis risks among the respondents was 60 points (full score is 80 points), with 50–59 being the most common range (51.9%), followed by 60–69 points (43.5%), and 4.4% of cases had more than 70 points. A multivariate logistic regression model revealed that respondents’ age (40–49 vs. 18–29; odds ratio (OR) = 2.53, 95% confidence interval (CI) = 1.31–4.87), education level (senior high vs. primary and junior high, OR = 2.00, 95% CI = 1.03–3.89; college and above vs. primary and junior high, OR = 3.66, 95% CI = 1.84–7.31), experience in undergoing a bone density test (OR = 1.94, 95% CI = 1.28–2.93), and poor physical fitness status (OR = 0.64, 95% CI = 0.43–0.95) were the significant predictors of the osteoporosis health literacy level. The osteoporosis health literacy of institutional caregivers is moderate, and there are many items that are worthy of attention in future health promotion programs. This study highlights risk factors related to a lower level of osteoporosis healthy literacy such as older age, less education, no experience of bone density test, and poor physical fitness that highlight the need to raise further awareness in order to improve caregivers’ bone health.